Evaluation of Results-Based Management in Optimizing the efficiency of public expenditure - SALIM , Chaimae; KHARISS , Mohammed (Revue Internationale des Sciences de Gestion, 2026)
This article examines the impact of results-based management on the efficiency of public spending within the frameperfowork of budgetary reforms undertaken by the Moroccan administration. Relying on a qualitative methodology, the research combines a documentary review of budgetary texts and official reports with a series of semi-structured interviews conducted with eight program managers from various ministries. The findings show that RBM has helped strengthen public performance through several levers: the clarification of objectives, the introduction of performance indicators, three-year budget programming, and the initial steps toward increased accountability of stakeholders. However, certain limitations remain, particularly regarding the quality of indicators, the effectiveness of monitoring and evaluation, the unfinished modernization of internal and external controls, and the weak performance culture within some administrations. The study highlights the need for stronger political commitment, support for change management, and better alignment between strategic planning and budget allocation. These results underscore that while RBM holds significant potential, it requires structural and cultural adjustments to fully achieve its goals in terms of efficiency and accountability.